67 ABNORMAL CYCLIC ADENOSINE MONOPHOSPHATE PRODUCTION IN HUMAN CORTICAL FRAGILE X NEURAL TISSUE: A PROOF OF PRINCIPLE STUDY. (1st March 2006) - Kelley, D. J.; Bhattacharyya, A.; Yin, J. C.; Oakes, T. R.; Chung, M. L.; Dalton, K. M.; Christian, B. T.; Davidson, R. J.
Abstract : Fragile X syndrome, the most common inheritable cause of mental retardation, is due to a CGG trinucleotide amplification on the X chromosome (Xq27.3) in the 59 untranslated region of the fragile X mental retardation 1 gene (FMR1) that suppresses production of the fragile X mental retardation protein (FMRP). Based on a decade of studies by Berry-Kravis who established the cyclic AMP (cAMP) cascade as dysfunctional in fragile X using a variety of non-neuronal cell types and who identified a direct relationship between levels of FMRP expression and cAMP levels in a mouse neural cell line overexpressing FMRP (Berry-Kravis and Ciurlionis, 1998), we hypothesized that human fragile X neural tissue would produce less cyclic AMP upon stimulation. Using an assay in which reductions in fluorescence intensity are associated with increasing cAMP levels (Mediomics, LLC), we quantified cAMP levels in neurospheres (NS) and differentiated cells (DC) from the human cortical fragile X (M049) and control (M037, M045, M046) fetal stem cell lines incubated with the phosphodiesterase inhibitor IBMX (3-isobutyl-1-methyl≠xanthine) in the presence or absence of forskolin, an adenylate cyclase agonist. As hypothesized, the fragile X differentiated cell line (fractional decrease in raw fluorescence [FDRF] = 0.32) shows a stimulated cAMP production that is reduced relative to the three differentiated control stem cell lines (mean FDRF ± SD = 0.70 ± 0.09). When differentiated cells are compared to neurospheres, all three control cell lines showed a marked increase in the levels of cAMP production in differentiated cells compared to undifferentiated neurospheres (mean FDRF difference [DC-NS] = 0.52); however, stimulated cAMP levels in differentiated cells and neurospheres are comparable in the fragile X line (FDRF difference [DC-NS] = 0.05). To our knowledge, these results are the first demonstration of an altered cAMP cascade in human fragile X neural tissue and suggest a developmental role for FMRP in the cAMP cascade. With only one human fragile X fetal stem cell line available, these results require replication with more fragile X neural tissue samples as they become available. Nevertheless, this proof of principle study identifies the human fragile X cAMP cascade as a potentially useful pharmacotherapeutic target that deserves further investigation.